Novel series fed dual band circular polarization antenna for navigational satellite system - Zalak Patel; Ashish Sarvaiya (Universitas Ahmad Dahlan, 2022)
A novel series fed dual band stacked microstrip patch antenna (SMPA) offering circular polarization (CP) over wide beam is proposed for Indian regional navigation satellite system (IRNSS). The antenna is designed to function at far apart dual frequencies 1.176 GHz (L5 band) and 2.492 GHz (S band) intended for the receiver terminals of IRNSS system. The dual band performance with large frequency ratio (about 1:2.1) has been obtained by two stacked patches with an air layer between them. The square notches at the corners along the diagonal of lower square patch, one sided corner truncation along the diagonal of upper square patch and feeding along central axis is used to obtain CP (with axial ratio < 2) at both the operating bands. The square patches are excited with novel series feed technique. The proposed novel antenna has been designed, simulated and developed to meet the stringent design requirements for IRNSS navigation system. The antenna has achieved an impedance bandwidth of 2.6% and 2.2% at L5 and S band frequency respectively. It possesses positive gain beamwidth of 120and 3 dB axial ratio beamwidth of 120◦ and 60◦ at L5 and S band frequencies respectively.